A combined mass spectrometry strategy for complete posttranslational modification mapping of Neisseria meningitidis major pilin. (8th November 2013) - Gault, Joseph; Malosse, Christian; Duménil, Guillaume; Chamot‐Rooke, Julia
<x xml:space="preserve">Abstract</x> Herein, we report a new approach, based on the combination of mass profiling and tandem mass spectrometry, to address the issue of localising all post‐translational modifications (PTMs) on the major pilin protein PiIE expressed by the pathogenic Neisseria species. PilE is the main component of type IV pili; filamentous organelles expressed at the surface of many bacterial pathogens and important virulence factors. Previous reports have shown that PilE can harbour various combinations of PTMs and have established strong links between PTM and pathogenesis. Complete PTM mapping of proteins involved in bacterial infection is therefore highly desirable. The methodology we propose here allowed us to fully characterise the PilE proteoforms of Neisseria meningitidis strain 8013, definitively identifying all PTMs present on all proteoforms and localising their position on the protein backbone. These modifications include a processed and methylated N‐terminus, disulfide bridge, glycosylation and glycerophosphorylation at two different sites. A key element of our approach is high resolution, intact mass measurement of the proteoforms, a piece of information completely lacking in all classical bottom–up proteomics strategies used for PTM analysis and without which it is difficult to ensure complete PTM mapping. Copyright © 2013 John Wiley & Sons, Ltd.